An overview of key industrial product citric acid production by Aspergillus niger and its application - Latif, Ambreen; Hassan, Noor; Ali, Hazrat; Niazi, Muhammad Bilal Khan; Jahan, Zaib; Ghuman, Iqra Latif; Hassan, Farwa; Saqib, Anam (Journal of industrial microbiology & biotechnology, 2025)
Abstract